The efficacy and safety of Ginkgo biloba L. leaves extract combined with ACEI/ARB on diabetic kidney disease: a systematic review and meta-analysis of 41 randomized controlled trials - Zhang, Zehua; Tang, Shiyun; Liu, Shiyu; Leng, Yulin; Fu, Xiaoxu; Xie, Hongyan; Gao, Hong; Xie, Chunguang (Frontiers in Pharmacology, 2025)
BackgroundDiabetic kidney disease (DKD) has become the leading cause of end-stage renal disease in the world. However, the current conventional approaches have not yet achieved satisfactory efficacy. As one of the most influential products in botanical medicine, Ginkgo biloba L. leaves extract (GBE) demonstrates various pharmacological effects on DKD and is gradually used as an adjunctive therapy for this disease. A comprehensive analysis is necessary to evaluate the efficacy and safety of GBE as an adjuvant treatment for DKD.ObjectiveThis meta-analysis aimed to evaluate the efficacy and safety of GBE as a supplementary treatment to conventional renin-angiotensin-aldosterone system inhibitors for DKD patients, providing a reference for subsequent research and clinical practice.MethodsThis study has been registered in PROSPERO as CRD42023455792. Ten databases were searched from their inception to 21 July 2023. Randomized controlled trials about GBE and DKD were included. Review Manager 5.4 and Stata 16.0 were employed to conduct the analysis. Heterogeneity was assessed through the χ2 test and the I2 test, and the effect model was chosen accordingly. Meta-regression and subgroup analysis were performed to investigate the sources of heterogeneity and the influence of different factor levels on efficacy. The publication bias was evaluated with the funnel plot and Egger’s test, and the evidence quality was evaluated by the Grading of Recommendations Assessment, Development and Evaluation (GRADE) method.ResultsA total of 41 studies with 3,269 patients were finally enrolled in this study. None of the included studies reported whether renal or cardiovascular disease progression events occurred. Compared with angiotensin-converting enzyme inhibitor (ACEI)/angiotensin II receptor blocker (ARB) alone, the combination with GBE was more beneficial in improving urinary albumin excretion rate (UAER) [mean difference (MD) = -22.99 μg/min, 95% confidence interval (CI): −27.66 to −18.31, p < 0.01], serum creatinine (SCr) [MD = −8.30 μmol/L, 95% CI: −11.55 to −5.05, p < 0.01], blood urea nitrogen (BUN) [MD = −0.77 mmol/L, 95% CI: −1.04 to −0.49, p < 0.01], 24-hour urinary total protein (24hUTP) [MD = −0.28 g/d, 95% CI: −0.35 to −0.22, p < 0.01], cystatin C (Cys-C) [MD = −0.30 mg/L, 95% CI: −0.43 to −0.17, p < 0.01], total cholesterol (TC) [MD = −0.69 mmol/L, 95% CI: −1.01 to −0.38, p < 0.01], triglyceride (TG) [MD = −0.40 mmol/L, 95% CI: −0.56 to −0.23, p < 0.01], low-density lipoprotein cholesterol (LDL-C) [MD = −0.97 mmol/L, 95% CI: −1.28 to −0.65, p < 0.01], fasting blood glucose (FBG) [MD = −0.30 mmol/L, 95% CI: −0.54 to −0.05, p = 0.02], hematocrit [MD = −4.58%, 95% CI: −5.25 to −3.90, p < 0.01] and fibrinogen [MD = −0.80 g/L, 95% CI: −1.12 to −0.47, p < 0.01]. No significant improvement was found in 2-hour postprandial glucose (2hPG), glycated hemoglobin (HbA1c), diastolic blood pressure (DBP) and systolic blood pressure (SBP). No significant difference was detected in adverse events.ConclusionCombining GBE with ACEI/ARB may improve UAER, SCr, BUN, 24hUTP, Cys-C, TC, TG, LDL-C, hematocrit and fibrinogen in DKD patients. It also seems beneficial for oxidative stress and inflammation but has minimal impact on glucose and blood pressure. Combined GBE therapy is generally tolerated, but safety monitoring remains essential during its use. More long-term high-quality clinical studies and in-depth molecular research are still necessary to provide stronger evidence regarding the benefits and safety of GBE in DKD.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=455792, identifier CRD42023455792